Green Green work and Organizational Change: Strategies for Adapting to Environmental Transitions - Mohamed Maamerie (Sociedad & Tecnología, 2025)
The study "Green Work and Organizational Change: Strategies for Adapting to Global Environmental Transitions" addresses the impact of environmental transitions on organizational structures and labor markets, focusing on the adaptation of organizations through the adoption of green work practices. The study reviews the causes of environmental transitions, such as climate change and resource depletion, and their impact on the labor market and organizational structure. It also focuses on adaptation strategies, including the adoption of green work practices, organizational restructuring, and environmental innovation. The study further examines the challenges organizations face, such as financial and cultural pressures, the role of leadership in driving change, and highlights successful experiences while emphasizing the importance of collaboration between the public and private sectors to achieve environmental sustainability.